ZFAS1/STAT3 axis modulates imatinib resistance of chronic myeloid leukemia cells through glucose metabolism reprogramming - Yang, Lan; Han, Yanqiu (Frontiers in Oncology, 2025)
BackgroundChronic myeloid leukemia (CML) is a myeloproliferative neoplasm characterized by the presence of the Philadelphia chromosome (chromosome 22). This cytogenetic abnormality gives rise to the BCR::ABL1 fusion gene, which encodes the constitutively active BCR-ABL1 protein tyrosine kinase, driving uncontrolled proliferation and impaired apoptosis of hematopoietic stem and progenitor cells, leading to leukemogenesis. Imatinib mesylate (IM), a first-generation tyrosine kinase inhibitor (TKI) specifically targeting the BCR-ABL1 oncoprotein, represents the standard first-line therapy for patients with CML. However, imatinib resistance remains a major therapeutic challenge.ObjectiveThis study aims to elucidate the role of the ZFAS1/STAT3 signaling axis in mediating imatinib resistance in CML by promoting metabolic reprogramming, with a particular focus on alterations in glucose metabolism.MethodsImatinib-resistant (IM-R) K562 cells were used to investigate the functional role of ZFAS1gene. Following ZFAS1 knockdown, assessments of cell viability, apoptosis, and glucose metabolism were performed. The interaction between ZFAS1 and IGF2BP2, as well as its regulatory effect on STAT3 expression and glycolysis-related genes (including HIF1α, LDHA, and PDK1) were examined using qRT-PCR and western blotting. Additionally, the impact of STAT3 overexpression and glycolysis inhibition (2-DG) on IM sensitivity were examined.ResultsOur findings revealed that ZFAS1 expression was significantly upregulated in IM-R CML patient samples and IM-R K562 cells. Silencing of ZFAS1 enhanced cellular sensitivity to IM, inhibited glucose metabolism reprogramming, and promoted apoptosis. Mechanistically, ZFAS1 was found to interact with IGF2BP2, facilitating the stabilization of STAT3 mRNA and leading to increased STAT3 expression. This, in turn, resulted in the upregulation of key glycolytic genes. Overexpression of STAT3 reversed the effects of ZFAS1 knockdown by restoring glycolytic activity and re-establishing IM resistance. Additionally, 2-DG treatment effectively reversed STAT3-induced IM resistance by inhibiting glycolysis.ConclusionThese findings demonstrate that the ZFAS1/STAT3 signaling axis contributes to imatinib resistance in CML through the modulation of glucose metabolism. Targeting this regulatory pathway may represent a novel therapeutic strategy to overcome TKI resistance in CML.